Diversity exists in development parameters and enhancement of antioxidant mechanisms of some einkorn and bread wheats under combined water deficits and salt stress - Pehlivan Karakas, Fatma; Bozat, Bihter Gokce; Aslan, Didem; Zencirci, Nusret (Progress in Nutrition, 2018)
Introduction. Climatic changes worsen the production of wheat, an important stable crop  while improving its some nutritional quality characteristics. Methods. Therefore, the purpose here was to evaluate some yield limiting factors as well as some quality characteristics in 8 bread wheat (Triticum aestivum L.) cultivars (Kıraç – 66, Kenanbey, Flamura - 85, Momtchill, Bayraktar – 2000, Tosunbey, Pandas, and Pehlivan) and 8 einkorn (Triticum monococcum spp. monococcum) populations (Populations – 4, 5, 6, 9, 10, 11, 14, and 15) under three different osmotic pressures (0.0 MPa., -0.5 MPa., or -1.0 MPa.) and three different salt concentrations [0.0 (distilled water), 50 mM or 100 mM NaCl]. Moreover, total phenolic content (TPC) and total flavonoid content (TFC), and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activities were determined. Results. Among bread wheat cultivars, Pandas had the longest shoot length, root length, the heaviest fresh shoot weight, dry shoot weight, and fresh root weight in the control group. In the einkorn populations, Pop – 6 had the longest shoot length, root length, the heaviest fresh shoot weight, dry shoot weight, and fresh root weight again in the control group. The heaviest dry root weight was obtained in Momtchill and Pop – 9 under drought stresses. The TPC was the highest in Kıraç - 66 and in Pop – 10 under salt stress and the TFC was in Pehlivan under salt stress. The methanol extracts of Kıraç – 66, Pop – 9, and Pop – 15 obtained under salt stress had stronger free radical scavenging activity than by ascorbic acid. Conclusion: Kıraç – 66 had the highest free radical scavenging antioxidant activity under salt stress and higher secondary metabolite products (as flavonoids), which indicated the highest tolerance system under both drought and salt  stress. Kıraç – 66, which was improved for poorer, drier, and cooler lands had better root and metabolite production under combined drought and salt stress as expected.